1996
DOI: 10.1111/j.1532-950x.1996.tb01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Pulmonary Effects of Sevoflurane Anesthesia in Horses

Abstract: The effects of 1.0, 1.5, and 2.0 minimum alveolar concentration (MAC) of sevoflurane on hemodynamic, pulmonary and blood chemistry variables were measured during spontaneous and controlled ventilation in healthy horses. Sevoflurane was the only anesthetic drug administered to the horses. In a dose-dependent manner, sevoflurane significantly decreased (P < .05) mean arterial blood pressure, cardiac output, and stroke volume. There was a progressive decrease in peripheral vascular resistance and an increase in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 16 publications
14
72
1
Order By: Relevance
“…The results of the study showed no statistically significant differences in cardiovascular or respiratory effects when comparing sevoflurane to isoflurane, which are consistent with previous reports in dogs, sheep, goats, humans and horses (Aida et al, 1996;Ebert et al, 1995;Hikasa et al, 1998;Matthews et al, 1998;Mutoh et al, 1997). Attempts to stand and recovery times appeared to occur faster for sevoflurane upon review of the data, although not statistically significant.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The results of the study showed no statistically significant differences in cardiovascular or respiratory effects when comparing sevoflurane to isoflurane, which are consistent with previous reports in dogs, sheep, goats, humans and horses (Aida et al, 1996;Ebert et al, 1995;Hikasa et al, 1998;Matthews et al, 1998;Mutoh et al, 1997). Attempts to stand and recovery times appeared to occur faster for sevoflurane upon review of the data, although not statistically significant.…”
Section: Resultssupporting
confidence: 82%
“…In dogs, it has been suggested that the differences in vagolytic activity of the inhalation anesthetics is responsible for the increase in HR observed (Steffey and Mama, 2007). In horses HR increased as the concentration of sevoflurane increased above 1 MAC, but the differences were not significant (Aida et al, 1996). In the present study, heart rate remained steady throughout the surgery and there was no statistical differences noted between sevoflurane and isoflurane.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations